2018
DOI: 10.1111/bph.14129
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin inhibits myeloid differentiation protein 2 to prevent LPS‐induced acute lung injury

Abstract: Our studies have uncovered the mechanism underlying the biological activity of shikonin in ALI and suggest that the targeting of MD2 may prove to be beneficial as a treatment option for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 71 publications
1
34
0
1
Order By: Relevance
“…NF-κB plays an important role in regulating of proinflammatory mediators in ALI ( Zhu et al, 2017 ; Zhang et al, 2018 ). NF-κB is activated by various stimuli such as cytokines, ROS, bacterial or viral products ( Zhao M.X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB plays an important role in regulating of proinflammatory mediators in ALI ( Zhu et al, 2017 ; Zhang et al, 2018 ). NF-κB is activated by various stimuli such as cytokines, ROS, bacterial or viral products ( Zhao M.X.…”
Section: Discussionmentioning
confidence: 99%
“…Activated NF-κB translocates into the nucleus where it triggers the transcription of specific genes such as TNF-α, IL-1β, and IL-6 ( Tang et al, 2017 ). NF-κB binding sequences have also been identified in proinflammatory genes such as iNOS and COX-2 ( Zhang et al, 2018 ). The protective effects of CH on LPS-induced endotoxic shock can be attributed to attenuating inflammatory cytokines and inhibition of the expression of NF-κB ( Niu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notedly, the binding site of Luteolin or Diacerein to hMD‐2 was identical to that of known MD‐2 inhibitor Shikonin (Figure 3E and Figure S4C, Supporting Information). [ 21 ] Interestingly, the chemical structures of Luteolin and Shikonin were similar (Figure S2A,E, Supporting Information). Fenbufen, a compound without inhibition activity for TLR4 (Figure S1, Supporting Information), had stochastic binding sites in the interface of hMD‐2 (Figure 3F) as a negative control in this docking assay.…”
Section: Resultsmentioning
confidence: 92%
“…Myeloid differentiation 2 (MD2), an accessory protein of toll-like receptor 4 (TLR4), is vital to mediating the lipopolysaccharide (LPS)/TLR4 acute inflammatory signaling [7,8]. Increasing evidence has shown that MD2 is associated with numerous acute and chronic inflammatory responses, and is considered a potential and meaningful therapeutic target for several inflammatory diseases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%